Effect of School Facilities, Tuition Fees And School Location On Decision Making of Students To Continue Education Toal Ulum Integrated High School - Satria Lubis, Andrew; Amalia, Alfi; Simanjuntak, Saroha (Journal Of Management Analytical and Solution (JoMAS), 2021)
This study aims to analyze and also find out how the influence of school facilities and school fees on the decision making of students to continue their education to SMA Al Ulum Terpadu. This study used 55 grade X students of SMA Al Ulum Terpadu as subjects. The type of research used is Descriptive-Quantitative  research  and  descriptive explanatory.  Data  collection was  conducted  by interview documentation and survey by distributing questionnaires to 51 students of grade X SMA Al Ulum Terpadu using completing échantillonnage techniques. Data analysis techniques used are multiple linear regression using SPPS 25 Software. The results showed that school facilities partially had a positive and significant effect on the decision making of students continuing school at SMA Al- Ulum Terpadu. The cost of education is partially negative and significant to the decision of students to continue  their  schooling  at  SMA  Al-Ulum  Terpadu.  The  location  of  the  school  is  partially insignificant to the decision of students to continue their schooling at SMA Al-Ulum Terpadu. School facilities, tuition fees and school locations simultaneously have a significant effect on the decision making of students continuing school at SMA Al-Ulum Terpadu